Composite material with heavy oil desulfurization function and preparation method and application thereof
By using composite materials prepared by alumina, silicon oxide, titanium oxide and sulfur absorption components, the problem of difficulty in reducing sulfur content in heavy oil is solved, efficient desulfurization and low-cost production are achieved, and it is suitable for the production of residue-type ship combustion.
Patent Information
- Application Number
- CN202111632846.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-29
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2041-12-29
AI Technical Summary
The prior art is difficult to effectively reduce the sulfur content of heavy oil, especially in the production process for residue-type ship combustion, and the existing desulfurizers are inefficient and costly in heavy oil.
Using a composite material, which includes alumina, silicon oxide, titanium oxide, sulfur absorbing components such as zinc oxide and Ni, and optional active aids, the crushing strength and desulfurization efficiency of the composite material are improved by specific preparation methods and reaction conditions.
It achieves efficient desulfurization of heavy oil, reduces the viscosity of heavy oil, and increases the desulfurization rate by more than 84%, while reducing the hydrogen consumption and extending the service life of the composite material.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fuel oil desulfurization, and in particular to a composite material with heavy oil desulfurization function and a preparation method and application thereof. Background Art
[0002] Exhaust emissions from ships during navigation cause serious environmental pollution. Reducing the sulfur content in fuel is the most effective emission reduction measure. Therefore, increasingly stringent sulfur content standards have been formulated for marine fuel oil and emission control areas have been established. It is required that from 2020, global ships use fuel oil with a sulfur mass fraction of no more than 0.5wt% outside emission control areas. The continuous upgrading of sulfur content standards and the monitoring of emission control areas will pose severe challenges to shipowners and oil product sellers. The implementation of new standards and laws and regulations has raised the market access threshold. The use of low-sulfur fuel oil not only increases the cost of shipowners, but also the current supply of low-sulfur marine fuel oil in the market is obviously insufficient, and there are fewer low-sulfur blending components, which is difficult to meet global market demand, mainly due to the high sulfur content of crude oil in most production areas.
[0003] Residual marine fuel with a sulfur mass fraction below 1.0wt% can also be produced using low-sulfur residual oil, but the output is relatively low. It is difficult to directly produce residual marine fuel with a sulfur mass fraction below 0.5wt% using the current blending components, and low-sulfur residual oil must be used for blending production. The existing process routes for producing residual marine fuel with a sulfur mass fraction below 0.5wt% mainly include: (1) replacing low-sulfur crude oil and using low-sulfur straight-run residual oil to blend and produce residual marine fuel. However, due to the high price of low-sulfur crude oil and limited resources, the production cost of residual marine fuel will be greatly increased, and this route is not suitable for producing residual marine fuel with lower value; (2) desulfurizing high-sulfur residual oil and using low-sulfur secondary processed residual oil to blend and produce residual marine fuel. This route is rich in resources, but the desulfurization cost is relatively high. Therefore, exploring and developing low-sulfur and low-cost fuel oil production technology and reducing the sulfur content in the main components of blended marine fuel oil are currently important tasks in the scientific research and production of marine fuel oil. The hydrodesulfurization of residue oil, which is currently widely used in industry, has the problems of harsh reaction conditions and high energy consumption. In addition, due to the stereo effect of the alkyl substituents, the efficiency of hydrodesulfurization technology in removing thiophenes and thiophene derivatives is very limited.
[0004] CN201410254990.1 discloses a fuel oil deep adsorption desulfurization catalyst, the catalyst includes active components, sulfur adsorbent, binder, wherein the active component is one or more of Ni, Co, Cu, W, Mo oxides, the sulfur adsorbent is at least one of Mg, Ca, Zn, Ce, Fe, Mn, Ti oxides, the mass percentage of the active component is 2wt%-50wt%, the mass percentage of the sulfur adsorbent is 20wt%-90wt%, and the rest is binder, the binder is a mixture of one or more of alumina, pseudo-boehmite, kaolin, montmorillonite, bentonite, cloud clay, diatomite, silica sol, silica gel, expanded perlite. The catalyst has a good desulfurization effect when used for light oils such as gasoline, diesel and kerosene, but when the catalyst is used for desulfurization of heavy oil, the desulfurization efficiency is greatly reduced, and the heavy oil after desulfurization cannot meet the requirements of residual ship fuel.
[0005] There are few studies on the desulfurization of heavy oil in the prior art, and most of the research focuses on the desulfurization of light oil (gasoline, diesel, kerosene and hydrocarbon oil, etc.). Since heavy oil contains large molecular sulfides, the desulfurizers generally suitable for light oil are less effective when used for desulfurization of heavy oil. Therefore, with the upgrading of global ship emission control standards, it is necessary to develop a desulfurizer suitable for desulfurization of heavy oil. Summary of the invention
[0006] The purpose of the present invention is to overcome the above problems existing in the prior art and to provide a composite material with heavy oil desulfurization function and a preparation method and application thereof.
[0007] In the adsorption desulfurization catalyst with zinc oxide and Ni as sulfur absorption components, during the reaction adsorption desulfurization process, the sulfur in the sulfide molecules, under the action of the catalyst, undergoes a multi-step reaction and finally reacts with the zinc oxide in the catalyst to generate zinc sulfide, thereby adsorbing the sulfur on the catalyst in the form of zinc sulfide to achieve the purpose of desulfurization. However, there are two problems with this type of adsorption desulfurization catalyst when used for heavy oil adsorption desulfurization: first, the heavy oil has a high viscosity and slow diffusion, which restricts the desulfurization ability of the catalyst; second, there is a strong interaction between the adsorption sulfur absorption component ZnO and the carrier Al2O3, which is easy to form zinc aluminum spinel during the adsorption desulfurization reaction and regeneration process, causing part of ZnO to lose its desulfurization and sulfur storage capabilities, thereby gradually deactivating the adsorption desulfurization catalyst. After Al2O3 and ZnO generate zinc aluminum spinel, the strength of the catalyst is further reduced.
[0008] Therefore, the first aspect of the present invention provides a composite material with heavy oil desulfurization function, the composite material comprising aluminum oxide, silicon oxide, titanium oxide, a sulfur absorption component and an optional active additive, wherein the sulfur absorption component comprises zinc oxide and Ni, and the weight ratio of aluminum oxide, silicon oxide and titanium oxide is 1-15:1-10:1.
[0009] The second aspect of the present invention provides a method for preparing a composite material with heavy oil desulfurization function, the preparation method comprising: kneading and calcining aluminum oxide, silicon oxide, titanium oxide, zinc oxide, a nickel precursor and an optional active agent precursor, the amount of aluminum oxide, silicon oxide and titanium oxide being used so that the weight ratio of aluminum oxide, silicon oxide and titanium oxide in the obtained composite material is 1-15:1-10:1.
[0010] The third aspect of the present invention provides a composite material prepared by the preparation method described in the second aspect.
[0011] A fourth aspect of the present invention provides a method for desulfurizing heavy oil, the method comprising contacting the composite material according to the first aspect or the second aspect of claim with heavy oil for reaction;
[0012] Alternatively, the method comprises preparing the composite material according to the preparation method described in the second aspect, and then contacting the obtained composite material with heavy oil for reaction.
[0013] Through the above technical solution, the present invention achieves the following beneficial effects:
[0014] (1) The crushing strength of the composite material prepared by the method of the present invention is significantly improved, the crushing strength is greater than 20N / mm, and the specific surface area of the composite material is 110-140m 2 / g, pore volume is 0.3-0.4cm 3 / g, and the average pore size is 11-15nm.
[0015] (2) The composite material of the present invention is suitable for desulfurization of heavy oil. The composite material of the present invention can reduce the viscosity of heavy oil and can reduce the kinematic viscosity of heavy oil to 150-200 mm 2 / s, and the composite material of the present invention has a high desulfurization efficiency, and the desulfurization rate can reach more than 84%.
[0016] (3) The composite material of the present invention can effectively remove benzothiophene, dibenzothiophene, benzonaphthothiophene and macromolecular sulfides with higher condensation degree from heavy oil.
[0017] (4) The composite material of the present invention has good stability, and the desulfurization rate of the composite material after 60 times of regeneration is equivalent to that of the fresh composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 is the XRD spectrum of the fresh composite material;
[0019] Figure 2 is the XRD spectrum of the regenerated composite material. DETAILED DESCRIPTION
[0020] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0021] The pressures in the present invention are all gauge pressures.
[0022] The first aspect of the present invention provides a composite material with heavy oil desulfurization function, the composite material comprises aluminum oxide, silicon oxide, titanium oxide, a sulfur absorption component and an optional active additive, wherein the sulfur absorption component comprises zinc oxide and Ni, and the weight ratio of aluminum oxide, silicon oxide and titanium oxide is 1-15:1-10:1.
[0023] According to the present invention, preferably, the weight ratio of aluminum oxide, silicon oxide and titanium oxide is 1.3-6:1-4:1.
[0024] According to the present invention, preferably, the weight ratio of zinc oxide to Ni calculated as oxide is 1-50:1, preferably 5-13:1.
[0025] According to the present invention, preferably, the weight ratio of zinc oxide to titanium oxide is 1-50:1, preferably 2-25:1.
[0026] According to the present invention, preferably, the weight ratio of the titanium oxide to the active auxiliary agent calculated as metal oxide is 1:0.1-0.8, preferably 1:0.2-0.4.
[0027] According to the present invention, preferably, the active auxiliary agent is at least one of the Group VIII B metals, preferably Fe and / or Mn.
[0028] According to the present invention, preferably, the content of Ce in the composite material is less than 0.1 wt %, and preferably does not contain Ce.
[0029] According to the present invention, preferably, the content of RE (rare earth element) in the composite material is less than 0.1 wt %, and preferably does not contain RE.
[0030] According to the present invention, preferably, based on the total weight of the composite material, the content of aluminum oxide in the composite material is 5-50% by weight, preferably 10-30% by weight.
[0031] According to the present invention, preferably, the specific surface area of the composite material is 110-140m 2 / g, pore volume is 0.3-0.4cm3 / g, an average pore size of 11-15nm, and a crushing strength greater than 20N / mm, preferably 22-30N / mm.
[0032] According to the present invention, preferably, in the XRD spectrum of the composite material, diffraction peaks exist at 2θ of 31.5°±0.2°, 34.5°±0.1°, 36.2°±0.2°, 36.9°±0.3°, and 43.0°±0.2°.
[0033] The second aspect of the present invention provides a method for preparing a composite material with heavy oil desulfurization function, the preparation method comprising: kneading and calcining aluminum oxide, silicon oxide, titanium oxide, zinc oxide, a nickel precursor and an optional active agent precursor, the amount of aluminum oxide, silicon oxide and titanium oxide used is such that in the obtained composite material, the weight ratio of aluminum oxide, silicon oxide and titanium oxide is 1-15:1-10:1 (for example 1:1:1, 2:1:1, 3:2:1, 4:3:1, 5:4:1, 6:5:1, 7:6:1, 8:7:1, 9:8:1, 10:9:1, 15:10:1, 5.6:3.3:1, 1.3:1:1, 2.7:1.9:1, 1.8:1.4:1, 1.8:1.3:1, 2.7:1.8:1).
[0034] According to the present invention, preferably, the silicon oxide is provided in the form of calcined kaolin.
[0035] According to the present invention, preferably, the alumina is provided in the form of calcined kaolin and pseudo-boehmite.
[0036] According to the present invention, preferably, the amounts of aluminum oxide, silicon oxide and titanium oxide used are such that the weight ratio of aluminum oxide, silicon oxide and titanium oxide in the obtained composite material is 1.3-6:1-4:1.
[0037] According to the present invention, the pseudo-boehmite may be the pseudo-boehmite commonly used in the art. Preferably, the pseudo-boehmite has a pore volume of 0.4-0.6 mL / g (e.g., 0.4 mL / g, 0.45 mL / g, 0.5 mL / g, 0.55 mL / g, 0.6 mL / g) and a specific surface area of 180-260 m 2 / g(180m 2 / g, 200m 2 / g, 210m 2 / g, 220m 2 / g, 230m 2 / g, 240m 2 / g, 250m 2 / g, 260m 2 / g), and a gel index greater than 95% (e.g., 95.1%, 95.5%, 96%, 96.5%, 97%, 97.5%, 98%, 98.5%, 99%, 99.9%), preferably 95.1%-99.9%. Limiting the parameters of pseudo-boehmite within the above range can improve the strength of the composite material.
[0038] According to the present invention, preferably, the calcined kaolin is obtained by calcining kaolin at 500-700°C (e.g., 500°C, 550°C, 580°C, 590°C, 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, 660°C, 680°C, 700°C) for 2-6h (e.g., 2h, 3h, 3.5h, 4h, 4.5h, 5h, 6h); more preferably, the calcined kaolin is obtained by calcining kaolin at 550-650°C for 3-5h. The above method for preparing calcined kaolin can expose the groups in the inner layer of the original kaolin crystal, and the types and number of surface active sites are increased.
[0039] According to the present invention, preferably, the zinc oxide is nano zinc oxide; more preferably, the purity of the raw material providing the nano zinc oxide is greater than 96wt% (for example, 96.1wt%, 96.5wt%, 97wt%, 97.5wt%, 98wt%, 98.5wt%, 99wt%, 99.9wt%), preferably 96.1wt%-99wt%, and the number average particle size is less than or equal to 100nm (for example, 1nm, 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm), preferably 50-90nm.
[0040] According to the present invention, preferably, the amounts of zinc oxide and nickel precursors used are such that in the resulting composite material, the weight ratio of zinc oxide to Ni as oxide is 1-50:1 (e.g., 1:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 20:1, 30:1, 40:1, 50:1), preferably 5-13:1.
[0041] According to the present invention, preferably, the amount of zinc oxide and titanium oxide used is such that in the obtained composite material, the weight ratio of zinc oxide to titanium oxide is 1-50:1 (for example 1:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 20:1, 30:1, 40:1, 50:1), preferably 2-25:1.
[0042] According to the present invention, preferably, the amounts of titanium oxide and active agent precursor used are such that in the resulting composite material, the weight ratio of titanium oxide to the active agent calculated as metal oxide is 1:0.1-0.8 (e.g. 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8), preferably 1:0.2-0.4.
[0043] According to the present invention, preferably, the active agent in the active agent precursor is at least one of the Group VIII B metals, preferably Fe and / or Mn.
[0044] According to the present invention, preferably, the raw materials used in the preparation method do not include substances containing the Ce element.
[0045] According to the present invention, preferably, the raw materials used in the preparation method do not include substances containing RE (rare earth elements).
[0046] According to the present invention, preferably, the preparation method comprises the following steps:
[0047] (1) kneading aluminum oxide, silicon oxide, titanium oxide, zinc oxide and an optional binder and performing a first calcination;
[0048] (2) loading Ni on the first calcined product;
[0049] (3) Loading an active auxiliary agent on the product of step (2).
[0050] According to the present invention, preferably, the weight ratio of the binder to zinc oxide is 0.05-0.3:1 (e.g., 0.05:1, 0.1:1, 0.15:1, 0.2:1, 0.25:1, 0.3:1).
[0051] According to the present invention, the type of the binder may be a commonly used binder in the art. Preferably, the binder is a polymer binder, preferably at least one of methyl cellulose, sodium carboxymethyl cellulose and sesbania powder.
[0052] According to the present invention, preferably, the conditions for the first calcination include: a temperature of 400-700° C., preferably 450-650° C., and a time of 1-10 h, preferably 3-5 h.
[0053] According to the present invention, preferably, the kneaded material can be in the form of a wet mixture, a paste mixture, a kneaded body or a slurry, and the kneaded molding can be oil-ammonia column molding, oil-water column molding, oil column molding, rolling ball molding or extrusion ball molding, preferably extrusion ball molding. Through the molding, the mixture of aluminum oxide, silicon oxide, titanium oxide, zinc oxide and optional binder can be molded into a spherical or toothed ball shape, preferably with a particle diameter of 1.5-3 mm.
[0054] According to the present invention, preferably, the step (1) further comprises mixing a mixture of aluminum oxide, silicon oxide, titanium oxide, zinc oxide and an optional binder with nitric acid and water, and then kneading. More preferably, the weight ratio of the nitric acid to the pseudo-boehmite providing aluminum oxide is 0.4-0.8:1, preferably 0.5-0.7:1. More preferably, the amount of water is not limited, as long as it can meet the molding requirements, and further preferably, the weight ratio of water to zinc oxide is 0.7-1.3:1.
[0055] According to the present invention, preferably, the step (1) further comprises drying the kneaded product and then performing a first calcination, and the drying conditions comprise: first drying naturally at room temperature for 12-48 hours, and then drying at 60-120°C (preferably 80-110°C) for 3-24 hours (preferably 6-10 hours).
[0056] According to the present invention, preferably, the method of loading Ni on the first calcined product is: contacting the first calcined product with a solution containing a nickel precursor, and then performing a second calcination.
[0057] According to the present invention, preferably, the nickel precursor in the solution containing the nickel precursor is a water-soluble salt of nickel, more preferably nickel nitrate and / or nickel acetate. The water-soluble salt of nickel may contain crystal water. More preferably, the mass percentage of the nickel precursor in the solution containing the nickel precursor is 2wt%-20wt%.
[0058] According to the present invention, the contact method of the first calcined product with the solution containing the nickel precursor is not particularly limited, as long as the nickel precursor can be supported on the first calcined product. Preferably, the contact method is an impregnation method. More preferably, the conditions for contacting the first calcined product with the solution containing the nickel precursor include: a temperature of 15-90°C, preferably 40-65°C, and a time of 1-24h, preferably 6-12h.
[0059] According to the present invention, preferably, the conditions for the second calcination include: a temperature of 400-700° C., preferably 450-650° C., and a time of 1-10 h, preferably 3-5 h.
[0060] According to the present invention, preferably, the step (2) further comprises drying the contact product and then performing a second calcination, and the drying conditions comprise: first drying naturally at room temperature for 12-48 hours, and then drying at 60-120°C (preferably 80-110°C) for 3-24 hours (preferably 6-10 hours).
[0061] According to the present invention, preferably, the method of loading the active auxiliary agent on the product of step (2) is: contacting the product of step (2) with a solution containing a precursor of the active auxiliary agent, and then performing a third calcination.
[0062] According to the present invention, preferably, the active agent precursor in the solution containing the active agent precursor is a water-soluble salt of the active agent, more preferably a nitrate of the active agent; further preferably manganese nitrate and / or iron nitrate. More preferably, the mass percentage of the active agent precursor in the solution containing the active agent precursor is 0.5wt%-4wt%.
[0063] According to the present invention, the method for contacting the product of step (2) with the solution containing the coagent precursor is not particularly limited, as long as the coagent precursor can be supported on the product of step (2). Preferably, the contact method is an impregnation method. More preferably, the conditions for contacting the product of step (2) with the solution containing the coagent precursor include: a temperature of 15-90° C., preferably 40-65° C., and a time of 1-24 h, preferably 6-12 h.
[0064] According to the present invention, preferably, the conditions of the third calcination include: a temperature of 400-700° C., preferably 450-650° C., and a time of 1-10 h, preferably 3-5 h.
[0065] According to the present invention, preferably, the step (3) further comprises drying the contact product and then performing a third calcination, and the drying conditions comprise: first drying naturally at room temperature for 12-48 hours, and then drying at 60-120°C (preferably 80-110°C) for 3-24 hours (preferably 6-10 hours).
[0066] According to the present invention, when used, the Ni and the active auxiliary agent in the composite material are generally required to function in a reduced form. Therefore, preferably, the preparation method further comprises reducing the product of step (3) so that the Ni and the active auxiliary agent exist in a reduced form.
[0067] According to the present invention, preferably, the reduction conditions include: in a hydrogen-containing atmosphere, the reduction temperature is 300-500°C, preferably 350-450°C, the reduction pressure is 0-3MPa, preferably 0.5-1.5MPa, and the reduction time is 1-6h, preferably 2-4h; more preferably, the volume fraction of hydrogen in the hydrogen-containing atmosphere is 50v%-100v%, preferably 80v%-100v%; more preferably, the volume space velocity of hydrogen is 500-4000h -1 , preferably 1500-3000h -1 .
[0068] The third aspect of the present invention provides a composite material prepared by the preparation method described in the second aspect.
[0069] A fourth aspect of the present invention provides a method for desulfurizing heavy oil, the method comprising contacting the composite material according to the first aspect or the second aspect of claim with heavy oil for reaction;
[0070] Alternatively, the method comprises preparing the composite material according to the preparation method described in the second aspect, and then contacting the obtained composite material with heavy oil for reaction.
[0071] According to the present invention, the type of reactor used in the reaction can be a reactor commonly used in the art. Preferably, the reactor is a fixed bed reactor, a moving bed reactor and an ebullating bed reactor, and more preferably a moving bed reactor.
[0072] According to the present invention, preferably, the reaction conditions include: temperature of 300-550°C; preferably 400-450°C, pressure of 0.5-10MPa, preferably 3-7MPa, and mass space velocity of heavy oil of 0.1-1h -1 , preferably 0.4-0.6h -1 .
[0073] According to the present invention, preferably, the method further comprises introducing hydrogen during the reaction, and the volume ratio of hydrogen to heavy oil is 100-800: 1, preferably 300-500: 1. The composite material of the present invention can reduce the amount of hydrogen used.
[0074] According to the present invention, preferably, the viscosity of the heavy oil (measured according to GB / T 265-1988) is 550-600 mm 2 / s(e.g. 550mm 2 / s, 560mm 2 / s, 570mm 2 / s, 580mm 2 / s, 590mm 2 / s、600mm 2 / s), density is 0.9-1g / cm 3 (e.g. 0.9 g / cm 3 、0.91g / cm 3 、0.92g / cm 3 、0.93g / cm 3 、0.94g / cm 3 , 0.95g / cm 3 、0.96g / cm 3 , 0.97g / cm 3 、0.98g / cm 3 , 0.99g / cm3 , 1g / cm 3 ), preferably 0.95-1g / cm 3 .
[0075] According to the present invention, preferably, the sulfur content in the heavy oil is 2wt%-3wt% (e.g., 2wt%, 2.1wt%, 2.2wt%, 2.3wt%, 2.4wt%, 2.5wt%, 2.6wt%, 2.7wt%, 2.8wt%, 2.9wt%, 3wt%), preferably 2.5wt%-2.8wt%.
[0076] According to the present invention, preferably, the heavy oil contains at least one of carbon oxysulfide, carbon disulfide, mercaptans, hydrogen sulfide, thiophene and thiophene derivatives; more preferably, the thiophene derivatives include at least one of benzothiophene, dibenzothiophene, benzonaphthiophene, alkylbenzothiophene, alkyldibenzothiophene and alkylbenzonaphthiophene.
[0077] According to the present invention, preferably, the heavy oil is selected from at least one of wax oil, atmospheric residue oil and vacuum residue oil.
[0078] According to the present invention, preferably, the method further comprises: oxidizing the composite material after reacting with the heavy oil to oxidize the zinc sulfide in the desulfurized composite material into zinc oxide.
[0079] According to the present invention, preferably, the oxidation conditions include: in an oxygen-containing atmosphere, the oxidation temperature is 300-500°C, the oxidation pressure is 0-0.5MPa, and the oxidation time is 20-100h; more preferably, the oxygen-containing atmosphere is a mixture of oxygen and nitrogen, and the volume space velocity of the mixture is 1000-3000h -1 , the volume fraction of oxygen in the oxygen-containing atmosphere is 1v%-10v%.
[0080] According to the present invention, preferably, the method further comprises reducing the oxidized composite material, and then contacting the reduced product with heavy oil for reaction, so as to realize the recycling of the composite material; more preferably, the reduction conditions comprise: under a hydrogen-containing atmosphere, the reduction temperature is 300-500°C, preferably 350-450°C, the reduction pressure is 0-3MPa, preferably 0.5-1.5MPa, and the reduction time is 1-6h, preferably 2-4h; further preferably, the volume fraction of hydrogen in the hydrogen-containing atmosphere is 10v%-100v%, preferably 60v%-100v%; further preferably, the volume space velocity of hydrogen in the hydrogen-containing atmosphere is 500-4000h-1 -1 , preferably 1500-3000h -1 .
[0081] The present invention will be described in detail below through examples. In the following examples, the room temperature is about 25°C;
[0082] Unless otherwise specified, the pseudo-boehmite in the following examples was purchased from Zibo Yinghe Chemical Co., Ltd., model number YH-2, the content of alumina in the pseudo-boehmite was 70 wt%, 0.55 mL / g, and the specific surface area was 240 m 2 / g, and the melt index is 96%.
[0083] Unless otherwise specified, the purity of the zinc oxide powder in the following examples is 98 wt % and the number average particle size is 80 nm.
[0084] Other reagents were purchased from Aladdin Reagent Network.
[0085] Preparation Example 1
[0086] Preparation of calcined kaolin: 2000 g of kaolin was weighed and calcined at 600° C. for 4 h. The calcined kaolin had a silicon oxide content of 46 wt % and an aluminum oxide content of 51 wt %.
[0087] Example 1
[0088] (1) 90 g of pseudo-boehmite, 182 g of calcined kaolin, 28 g of titanium oxide, 80 g of sodium carboxymethyl cellulose and 600 g of zinc oxide powder were mixed evenly, and 432 g of water and 72 g of nitric acid were added. After mixing evenly, the mixture was squeezed into small balls with a particle diameter of 2 mm. The small balls were naturally dried at room temperature for 24 h, then dried at 100° C. for 8 h, and calcined at 550° C. for 4 h.
[0089] (2) Weigh 333 g of nickel acetate tetrahydrate, add 1700 g of water to prepare a solution, and place the pellets calcined in step (1) in the solution and immerse at 50° C. for 8 h. Then, naturally dry at room temperature for 24 h, dry at 80° C. for 10 h, and calcine at 500° C. for 4 h.
[0090] (3) Weigh 30.3 g of ferric nitrate, add 3900 g of water to prepare a solution, and place the pellets calcined in step (2) in the ferric nitrate solution at 60° C. for 6 h. Then, naturally dry at room temperature for 12 h, dry at 110° C. for 6 h, and calcine at 600° C. for 3 h to obtain a composite material precursor S1.
[0091] (4) The composite material precursor S1 was placed in a hydrogen atmosphere (hydrogen content of 80v%, hydrogen volume space velocity of 2000h-1) -1 ) under the conditions of a reduction pressure of 1 MPa and a reduction temperature of 400°C for 3 h to obtain a composite material S1.
[0092] Example 2
[0093] (1) 72 g of pseudo-boehmite, 357 g of calcined kaolin, 171 g of titanium oxide, 90 g of sodium carboxymethyl cellulose and 370 g of zinc oxide powder were mixed evenly, 465 g of water and 29 g of nitric acid were added, mixed evenly and squeezed into small balls with a particle diameter of 2 mm. The small balls were naturally dried at room temperature for 18 h, then dried at 80° C. for 10 h, and calcined at 450° C. for 5 h.
[0094] (2) Weigh 117 g of nickel nitrate hexahydrate, add 3800 g of water to prepare a solution, and place the pellets calcined in step (1) in the solution and immerse at 40° C. for 12 h. Then, naturally dry at room temperature for 36 h, dry at 90° C. for 7 h, and calcine at 550° C. for 3 h.
[0095] (3) Weigh 75.6 g of manganese nitrate, add 2000 g of water to prepare a solution, place the pellets calcined in step (2) in the solution and immerse at 50° C. for 10 h. Then naturally dry at room temperature for 24 h, then dry at 100° C. for 8 h, and calcine at 650° C. for 3 h to obtain a composite material precursor S2.
[0096] (4) The composite material precursor S2 was placed in a hydrogen atmosphere (hydrogen content of 60v%, hydrogen volume space velocity of 3000h-1) -1 ) under the conditions of a reduction pressure of 1.5 MPa and a reduction temperature of 450°C for 2 h to obtain a composite material S2.
[0097] Example 3
[0098] (1) 83 g of pseudo-boehmite, 250 g of calcined kaolin, 67 g of titanium oxide, 40 g of sodium carboxymethyl cellulose and 520 g of zinc oxide powder were mixed evenly, 419 g of water and 41.5 g of nitric acid were added, mixed evenly and squeezed into small balls with a particle diameter of 2 mm. The small balls were naturally dried at room temperature for 12 h, then dried at 110° C. for 6 h, and calcined at 650° C. for 3 h.
[0099] (2) Weigh 266 g of nickel acetate tetrahydrate, add 2300 g of water to prepare a solution, and place the pellets calcined in step (1) in the solution and immerse at 55° C. for 12 h. Then, naturally dry at room temperature for 18 h, then dry at 100° C. for 6 h, and calcine at 450° C. for 5 h.
[0100] (3) Weigh 45.4 g of ferric nitrate, add 3400 g of water to prepare a solution, place the pellets calcined in step (2) in the solution and immerse at 65° C. for 8 h. Then naturally dry at room temperature for 24 h, then dry at 80° C. for 10 h, and calcine at 550° C. for 4 h to obtain a composite material precursor S3.
[0101] (4) The composite material precursor S3 was placed in a hydrogen atmosphere (hydrogen content of 70v%, hydrogen volume space velocity of 2500h-1) -1 ) under the conditions of reduction pressure of 0.5 MPa and reduction temperature of 350°C for 4 hours to obtain composite material S3.
[0102] Example 4
[0103] (1) 77 g of pseudo-boehmite, 308 g of calcined kaolin, 115 g of titanium oxide, 50 g of sodium carboxymethyl cellulose and 450 g of zinc oxide powder were mixed evenly, 478 g of water and 46 g of nitric acid were added, mixed evenly and squeezed into small balls with a particle diameter of 2 mm. The small balls were naturally dried at room temperature for 36 hours, then dried at 100°C for 6 hours, and calcined at 550°C for 4 hours.
[0104] (2) Weigh 195 g of nickel nitrate hexahydrate, add 2500 g of water to prepare a solution, and place the pellets calcined in step (1) in the solution and immerse at 45° C. for 10 h. Then, naturally dry at room temperature for 24 h, then dry at 110° C. for 6 h, and calcine at 450° C. for 5 h.
[0105] (3) Weigh 50.4 g of manganese nitrate, add 2500 g of water to prepare a solution, and place the pellets calcined in step (2) in the solution and immerse at 60° C. for 12 h. Then, naturally dry at room temperature for 18 h, then dry at 90° C. for 10 h, and calcine at 600° C. for 4 h to obtain a composite material precursor S4.
[0106] (4) The composite material precursor S4 was placed in a hydrogen atmosphere (hydrogen content of 90v%, hydrogen volume space velocity of 2000h-1) -1 ) and reduced for 3 h under the conditions of a reduction pressure of 1 MPa and a reduction temperature of 400°C to obtain a composite material S4.
[0107] Example 5
[0108] (1) 62 g of pseudo-boehmite, 246 g of calcined kaolin, 92 g of titanium oxide, 60 g of sodium carboxymethyl cellulose and 530 g of zinc oxide powder were mixed evenly, 490 g of water and 43 g of nitric acid were added, mixed evenly and squeezed into small balls with a particle diameter of 2 mm. The small balls were naturally dried at room temperature for 24 h, then dried at 110° C. for 7 h, and calcined at 450° C. for 5 h.
[0109] (2) Weigh 233 g of nickel acetate tetrahydrate, add 2000 g of water to prepare a solution, and place the pellets calcined in step (1) in the solution and immerse at 55° C. for 8 h. Then naturally dry at room temperature for 12 h, then dry at 100° C. for 10 h, and calcine at 550° C. for 3 h.
[0110] (3) Weigh 63 g of manganese nitrate, add 2000 g of water to prepare a solution, place the pellets calcined in step (2) in the solution and immerse at 65° C. for 10 h. Then naturally dry at room temperature for 24 h, then dry at 80° C. for 9 h, and calcine at 450° C. for 5 h to obtain a composite material precursor S5.
[0111] (4) The composite material precursor S5 was placed in a hydrogen atmosphere (hydrogen content of 100 v%, hydrogen volume space velocity of 3000 h -1 ) was reduced under the conditions of a reduction pressure of 1.5 MPa and a reduction temperature of 300°C for 4 hours to obtain a composite material S5.
[0112] Example 6
[0113] (1) 104 g of pseudo-boehmite, 312 g of calcined kaolin, 84 g of titanium oxide, 50 g of sodium carboxymethyl cellulose and 440 g of zinc oxide powder were mixed evenly, 427 g of water and 62 g of nitric acid were added, mixed evenly and squeezed into small balls with a particle diameter of 2 mm. The small balls were naturally dried at room temperature for 12 h, then dried at 110° C. for 10 h, and calcined at 650° C. for 3 h.
[0114] (2) Weigh 234 g of nickel nitrate hexahydrate, add 2300 g of water to prepare a solution, and place the pellets calcined in step (1) in the solution and immerse at 65° C. for 12 h. Then, naturally dry at room temperature for 12 h, then dry at 80° C. for 10 h, and calcine at 550° C. for 4 h.
[0115] (3) Weigh 60.6 g of ferric nitrate, add 2850 g of water to prepare a solution, and place the pellets calcined in step (2) in the solution and immerse at 55° C. for 8 h. Then, naturally dry at room temperature for 24 h, then dry at 110° C. for 7 h, and calcine at 500° C. for 5 h to obtain a composite material precursor S6.
[0116] (4) The composite material precursor S6 was placed in a hydrogen atmosphere (hydrogen content of 80v%, hydrogen volume space velocity of 1500h-1) -1 ) under the conditions of reduction pressure of 0.5 MPa and reduction temperature of 350°C for 4 hours to obtain the composite material S6.
[0117] Example 7
[0118] The composite material was prepared according to the method of Example 3, except that the calcined kaolin was calcined at 800° C. for 8 h to obtain the composite material S7.
[0119] Example 8
[0120] A composite material was prepared according to the method of Example 3, except that the amounts of zinc oxide and nickel acetate tetrahydrate were different, and the content of zinc oxide in the prepared composite material was 42.5% by weight, and the content of nickel oxide was 18% by weight, that is, the weight ratio of zinc oxide to nickel oxide was 2.36, to obtain composite material S8.
[0121] Example 9
[0122] The composite material was prepared by referring to the method of Example 3, except that the contents of the components in the prepared composite material precursor were different from those in Example 3. The contents of the components in the composite material precursor S9 are shown in Table 1.
[0123] Example 10
[0124] The composite material was prepared by referring to the method of Example 3, except that the contents of the components in the prepared composite material precursor were different from those in Example 3. The contents of the components in the composite material precursor S10 are shown in Table 1.
[0125] Embodiment 11
[0126] The composite material is prepared according to the method of Example 3, except that the pellets calcined in step (1) are placed in a mixed solution of nickel acetate tetrahydrate and ferric nitrate. The specific steps are as follows:
[0127] (1) 83 g of pseudo-boehmite, 250 g of calcined kaolin, 67 g of titanium oxide, 40 g of sodium carboxymethyl cellulose and 520 g of zinc oxide powder were mixed evenly, 419 g of water and 41.5 g of nitric acid were added, mixed evenly and squeezed into small balls with a particle diameter of 2 mm. The small balls were naturally dried at room temperature for 12 h, then dried at 110° C. for 6 h, and calcined at 650° C. for 3 h.
[0128] (2) Weigh 266 g of nickel acetate tetrahydrate and 45.4 g of ferric nitrate, add 2300 g of water to prepare a mixed solution of nickel acetate tetrahydrate and ferric nitrate, place the pellets calcined in step (1) in the solution and immerse at 55° C. for 12 h. Then naturally dry at room temperature for 18 h, then dry at 100° C. for 6 h, and calcine at 450° C. for 5 h. Obtain composite material precursor S11.
[0129] (3) The same as step (4) of Example 3. A composite material S11 is obtained.
[0130] Comparative Example 1
[0131] A composite material was prepared according to the method of Example 3, except that the pseudo-boehmite in step (1) was replaced by an equal weight of calcined kaolin to obtain a composite material D1.
[0132] Comparative Example 2
[0133] A composite material was prepared according to the method of Example 3, except that the calcined kaolin in step (1) was replaced with an equal weight of pseudo-boehmite, to obtain composite material D2.
[0134] Comparative Example 3
[0135] A composite material was prepared according to the method of Example 3, except that the calcined kaolin in step (1) was replaced by pseudo-boehmite, and the content of aluminum oxide in the pseudo-boehmite was 70 wt %, the pore volume was 0.48 mL / g, and the specific surface area was 210 m 2 / g, and the melt index was 95%, thereby obtaining a composite material D3.
[0136] Comparative Example 4
[0137] A composite material was prepared according to the method of Example 4, except that the titanium oxide in step (1) was replaced by an equal weight of calcined kaolin to obtain a composite material D4.
[0138] Comparative Example 5
[0139] A composite material D4 was prepared according to the method of Example 4, except that the titanium oxide in step (1) was replaced by an equal weight of pseudo-boehmite, to obtain a composite material D4.
[0140] Comparative Example 6
[0141] A composite material D6 was prepared according to the method of Example 5, except that step (2) was omitted and nickel was not impregnated, to obtain a composite material D6.
[0142] Test Case
[0143] (1) The composition of the composite material precursor prepared in the above-mentioned embodiment and comparative example is analyzed by X-ray fluorescence spectrometer. The sample to be tested is ground and melted by high-frequency melting machine, and the mold is cooled to make a sample. According to the selected analysis conditions on the X-ray fluorescence spectrometer, a working curve is made with the standard sample, and the content of each component is determined according to the working curve. Referring to the standard "NB / SH / T 0863-2013", the content of each component in the composite material precursor is shown in Table 1. Since the raw materials used contain a small amount of unavoidable impurities, the sum of the content of each component of the composite material precursor in Table 1 is less than 100%.
[0144] The specific surface area, pore size and pore volume of the composite material precursors prepared in the above examples and comparative examples were characterized by BET. A certain amount of the sample to be tested was weighed and vacuumed at 300°C for 4.0 hours, and then the N2 adsorption-desorption isotherm and pore size distribution of the composite material precursor were tested by Tri StarⅡ3020 (Mike Instrument Company, USA) automatic analyzer. The specific surface area, pore size distribution and pore volume of the sample were calculated by the BET equation and the BJH method, respectively, and the results are shown in Table 2.
[0145] The mechanical strength of the composite material precursor particles was measured using a universal automatic strength tester with a range of 0-500N and an accuracy of 0.1N. A single sample was placed between two rigid platforms, one of which remained stationary and the other moved axially downward at an extremely low speed. The crushing strength was determined as the maximum load measured before the particles broke. 50 regular particles were selected for each sample for strength testing to obtain representative mechanical properties. The crushing strengths of the composite material precursors prepared in the above embodiments and comparative examples are shown in Table 2.
[0146] Table 1
[0147]
[0148]
[0149] (2) Evaluation of composite material performance: The composite materials prepared in the above embodiments and comparative examples were evaluated using a fixed bed test apparatus. 200 g of the composite material was loaded into a fixed bed reactor and desulfurization reaction was carried out under the conditions of reaction temperature of 420° C., reaction pressure of 4 MPa, hydrogen flow rate of 35 L / h, and residual oil feed rate of 100 g / h. After 10 h of reaction, the total sulfur content of the heavy oil feedstock and the desulfurized product was measured, and the desulfurization rate was calculated. The results are shown in Table 2.
[0150] The total sulfur content in the liquid sample was determined by ultraviolet fluorescence using the American photonLAB total sulfur and total nitrogen analyzer at a temperature of 1000°C, argon at 30 psi, and oxygen at 10 psi, with reference to the standard "SH / T 0689-2000".
[0151] At a constant temperature of 40°C, measure the time it takes for a certain volume of liquid to flow through a calibrated glass capillary viscometer under gravity. The product of the capillary constant of the viscometer and the movement time is used to determine the kinematic viscosity of the liquid at this temperature. Refer to the standard "GB / T 265-1988 Determination of kinematic viscosity of petroleum products". Each sample is measured twice and the average value is taken. The dynamic viscosity of desulfurized heavy oil at 40°C is shown in Table 2.
[0152] The test raw material used was vacuum residue oil with a sulfur content of 2.7 wt% and a dynamic viscosity of 584 mm at 40 °C. 2 / s, density is 0.9952g / cm 3 .
[0153] Table 2
[0154]
[0155] As shown in Table 2, the crushing strength of the composite material prepared by the method of the present invention is above 20N, the desulfurization rate is above 84%, and the viscosity of the desulfurized product is lower than 200mm 2 ·s -1 The composite material of the present invention has good strength, which can prevent the composite material from breaking during or after filling; the composite material of the present invention has a high desulfurization rate, and the viscosity of the desulfurized product oil is significantly reduced, and has an obvious viscosity-reducing effect.
[0156] (3) regenerating the desulfurized composite material in step (2) in a fixed bed reactor, first oxidizing the desulfurized composite material to obtain an oxidized composite material, and then reducing the oxidized composite material to obtain a regenerated composite material, wherein the oxidation conditions include: in an oxygen-containing atmosphere (the oxygen-containing atmosphere is a mixture of oxygen and nitrogen, and the volume space velocity of the mixture is 3000h / min); -1 The oxidation was carried out under the conditions of 400°C and 0.5 MPa of oxidation pressure for 72 h. The reduction conditions included: in a hydrogen atmosphere (the volume fraction of hydrogen was 70 v%, the volume space velocity of hydrogen was 2000 h -1 ) under the conditions of reduction pressure of 0.75 MPa and reduction temperature of 400 °C for 3 h.
[0157] The regenerated composite material was desulfurized according to the desulfurization method of step (2) of the test example, and the desulfurization rate is shown in Table 3. Then, it was regenerated according to the regeneration method of step (3) of the test example, and the cycle was repeated.
[0158] It can be seen from Table 2 that the desulfurization rates of composite materials S1-S6, D1, D4, and D5 are above 80%, and the desulfurization rates of other composite materials are all lower than 80%, among which the crushing strength of composite material D1 is only 5N. Therefore, S1, S2, D4, and D5 are taken as examples to illustrate the regeneration performance of the composite materials prepared by the present invention.
[0159] Table 3
[0160]
[0161] As shown in Table 3, the desulfurization rate of the composite material prepared in Example 1-2 after 60 regenerations is basically the same as that of the fresh composite material, indicating that the composite material of the present invention has good stability. However, the desulfurization rate of the composite material prepared in Comparative Examples 4-5 after 15 regenerations is less than 40%, indicating that the composite material prepared in Comparative Examples has poor stability.
[0162] It is particularly noted that the desulfurization rates of the composite materials prepared in Examples 3-6 after being regenerated 60 times are equivalent to the desulfurization rates of the fresh composite materials; the desulfurization rates of the composite materials prepared in Examples 7-8 after being regenerated 60 times are lower; and the desulfurization rates of the composite materials prepared in Comparative Examples 1-3 and Comparative Example 6 after being regenerated 15 times are almost reduced to half of the desulfurization rates of the fresh composite materials, or even lower.
[0163] (4) The mechanical strength of the composite material after regeneration and oxidation in step (3) of the test example was measured using a universal automatic strength tester. The test method was the same as the test method for the mechanical strength of the composite material precursor particles in step (1). The results are shown in Table 4.
[0164] Table 4
[0165] Crushing strength(N) S1 after 60 regenerations 22 S2 after 60 regenerations 25 D4 after 15 regenerations 6 D5 after 15 regenerations 8
[0166] It can be seen from Table 4 that the crushing strength of the regenerated and oxidized composite materials S1 and S2 is almost the same as that of the fresh composite materials, while the crushing strength of the regenerated and oxidized composite materials D4 and D5 is significantly reduced.
[0167] (5) The crystal structure of the fresh composite materials prepared in the above embodiments and comparative examples and the composite materials after regeneration and oxidation in step (3) of the test example were characterized by XRD (X-Ray Diffraction). The measurement was carried out using a Japanese Rigaku D / max 2200PC X-ray powder diffractometer with a Cu target, a graphite monochromator, a scanning speed of 10 degrees / minute, a scanning step of 0.02 degrees, a voltage of 40 kV, and a current of 20 mA. The intensity and position of the diffraction peaks in the XRD spectrum were used for qualitative analysis to determine the type, structure, crystalline state, and state of element existence of the substance.
[0168] Figure 1 It is the XRD spectrum of the fresh composite material precursors prepared in Examples 1-2 and Comparative Examples 4-5. It can be seen from the figure that the main characteristic diffraction peaks in the fresh composite material precursors S1, S2, D4, and D5 are the zinc oxide crystal phase peaks (2θ is 31.5°, 34.4°, 36.2°) and the nickel oxide crystal phase peaks (2θ is 36.9°, 43.0°). The characteristic diffraction peak of ZnO is sharp and has high intensity, and it is the main active component.
[0169] Figure 2In the figure, (a) and (b) are XRD spectra of the composite materials of Examples 1-2 after 60 regeneration oxidations, and (c) and (d) are XRD spectra of the composite materials of Comparative Examples 4-5 after 15 regeneration oxidations. Compared with the fresh composite materials, the complexity of the spectra of the composite materials after regeneration oxidation is significantly increased. In addition to the regeneration products ZnO and NiO, new phases such as desulfurization products ZnS, ZnAl2O4, and Zn2SiO4 are also generated.
[0170] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A composite material having a heavy oil desulfurization function, characterized in that: The composite material comprises aluminum oxide, silicon oxide, titanium oxide, a sulfur absorbing component and an active additive, wherein the sulfur absorbing component comprises zinc oxide and Ni, and the weight ratio of aluminum oxide, silicon oxide and titanium oxide is 1.3-6:1-4:1; The weight ratio of zinc oxide to Ni in terms of oxide is 5-13:1; The weight ratio of zinc oxide to titanium oxide is 2-25:1; The weight ratio of the titanium oxide to the active auxiliary agent calculated as metal oxide is 1:0.2-0.4; The active additive is Fe and / or Mn; The specific surface area of the composite material is 110-140m 2 / g, pore volume is 0.3-0.4cm 3 / g, average pore size is 11-15nm, crushing strength is greater than 20N / mm; The silicon oxide is provided in the form of calcined kaolin; the aluminum oxide is provided in the form of calcined kaolin and pseudo-boehmite.
2. The composite material according to claim 1, wherein The content of Ce in the composite material is less than 0.1 wt %.
3. The composite material according to claim 2, wherein: The composite material does not contain Ce.
4. The composite material according to claim 1, wherein Based on the total weight of the composite material, the content of aluminum oxide in the composite material is 5-50 weight %.
5. The composite material according to claim 4, wherein Based on the total weight of the composite material, the content of aluminum oxide in the composite material is 10-30 weight %.
6. A method for preparing the composite material with heavy oil desulfurization function according to any one of claims 1 to 5, characterized in that: The preparation method comprises: (1) kneading aluminum oxide, silicon oxide, titanium oxide, zinc oxide and an optional binder and performing a first calcination; (2) loading Ni on the first calcined product; (3) Loading an active auxiliary agent on the product of step (2).
7. The preparation method according to claim 6, wherein: The silicon oxide is provided in the form of calcined kaolin; And / or, the alumina is provided in the form of calcined kaolin and pseudo-boehmite.
8. The preparation method according to claim 7, wherein: The pseudo-boehmite has a pore volume of 0.4-0.6 mL / g and a specific surface area of 180-260 m 2 / g, the gel index is greater than 95%; And / or, the calcined kaolin is obtained by calcining kaolin at 500-700° C. for 2-6 hours; And / or, the zinc oxide is nano zinc oxide.
9. The preparation method according to claim 8, wherein: The purity of the raw material of the nano zinc oxide is greater than 96wt%, and the number average particle size is less than or equal to 100nm.
10. The preparation method according to claim 6, wherein: The weight ratio of the binder to zinc oxide is 0.05-0.3:1; And / or, the binder is a polymer binder; And / or, the first calcination conditions include: temperature of 400-700° C. and time of 1-10 h.
11. The preparation method according to claim 10, wherein: The binder is at least one of methyl cellulose, sodium carboxymethyl cellulose and sesbania powder; And / or, the first calcination conditions include: temperature of 450-650° C. and time of 3-5 h.
12. The preparation method according to claim 6, wherein: The method of loading Ni on the first calcined product is: contacting the first calcined product with a solution containing a nickel precursor, and then performing a second calcination; and / or, the conditions for contacting the first calcined product with the solution containing a nickel precursor include: a temperature of 15-90° C. and a time of 1-24 h; And / or, the second calcination conditions include: temperature of 400-700° C. and time of 1-10 h.
13. The preparation method according to claim 12, wherein: The nickel precursor in the solution containing the nickel precursor is a water-soluble salt of nickel; and / or, the conditions for contacting the first calcined product with the solution containing a nickel precursor include: a temperature of 40-65° C. and a time of 6-12 h; And / or, the second calcination conditions include: temperature of 450-650° C. and time of 3-5 h.
14. The preparation method according to claim 6, wherein: The method of loading the active agent on the product of step (2) is: contacting the product of step (2) with a solution containing a precursor of the active agent, and then performing a third calcination; And / or, the conditions for contacting the product of step (2) with the solution containing the active agent precursor include: temperature of 15-90° C., time of 1-24 h; And / or, the conditions of the third calcination include: temperature of 400-700° C. and time of 1-10 h.
15. The preparation method according to claim 14, wherein: The active auxiliary agent precursor in the solution containing the active auxiliary agent precursor is a water-soluble salt of the active auxiliary agent; And / or, the conditions for contacting the product of step (2) with the solution containing the active agent precursor include: temperature of 40-65° C., time of 6-12 h; And / or, the conditions of the third calcination include: temperature of 450-650° C. and time of 3-5 h.
16. The preparation method according to claim 15, wherein: The active auxiliary agent precursor in the solution containing the active auxiliary agent precursor is a nitrate of the auxiliary agent.
17. The preparation method according to claim 6, wherein: The preparation method further comprises reducing the product of step (3) so that Ni and the active auxiliary agent exist in a reduced state.
18. The preparation method according to claim 17, wherein: The reduction conditions include: in a hydrogen-containing atmosphere, a reduction temperature of 300-500° C., a reduction pressure of 0-3 MPa, and a reduction time of 1-6 h.
19. The preparation method according to claim 18, wherein: The reduction conditions include: in a hydrogen-containing atmosphere, a reduction temperature of 350-450° C., a reduction pressure of 0.5-1.5 MPa, and a reduction time of 2-4 h.
20. The preparation method according to claim 18 or 19, wherein: The volume fraction of hydrogen in the hydrogen-containing atmosphere is 50-100v%.
21. The preparation method according to claim 20, wherein: The volume fraction of hydrogen in the hydrogen-containing atmosphere is 80-100v%.
22. The preparation method according to claim 18 or 19, wherein: The volume space velocity of the hydrogen is 500-4000h -1 .
23. The preparation method according to claim 22, wherein: The volume space velocity of the hydrogen is 1500-3000h -1 .
24. A method for desulfurizing heavy oil, characterized in that: The method comprises contacting the composite material according to any one of claims 1 to 5 with heavy oil for reaction; Alternatively, the method comprises preparing a composite material according to the preparation method according to any one of claims 6 to 23, and then contacting the obtained composite material with heavy oil for reaction.
25. The method according to claim 24, wherein: The reaction conditions include: temperature of 300-550°C, pressure of 0.5-10 MPa, mass space velocity of heavy oil of 0.1-1h -1 ; And / or, the method further comprises introducing hydrogen during the reaction, wherein the volume ratio of hydrogen to heavy oil is 100-800:1; And / or, the viscosity of the heavy oil is 500-600mm 2 / s, density is 0.9-1g / cm 3 ; And / or, the sulfur content in the heavy oil is 2-3wt%.
26. The method according to claim 25, wherein: The reaction conditions include: temperature of 400-450°C, pressure of 3-7 MPa, mass space velocity of heavy oil of 0.4-0.6 h -1 ; and / or, the volume ratio of hydrogen to heavy oil is 300-500:1; And / or, the viscosity of the heavy oil is 550-590 mm 2 / s, density is 0.95-1g / cm 3 .
27. The method according to claim 24, wherein: The method further comprises: oxidizing the composite material after contacting with the heavy oil to oxidize the zinc sulfide in the desulfurized composite material into zinc oxide.
28. The method according to claim 27, wherein: The oxidation conditions include: in an oxygen-containing atmosphere, an oxidation temperature of 300-500° C., an oxidation pressure of 0-0.5 MPa, and an oxidation time of 20-100 h.
29. The method according to claim 28, wherein: The oxygen-containing atmosphere is a mixture of oxygen and nitrogen, and the volume space velocity of the mixture is 1000-3000h -1 , the volume fraction of oxygen in the oxygen-containing atmosphere is 1-10v%.
30. The method according to any one of claims 27 to 29, wherein: The method further comprises reducing the oxidized composite material, and then contacting the reduced product with heavy oil for reaction, thereby realizing the recycling of the composite material.
31. The method according to claim 30, wherein: The reduction conditions include: under a hydrogen-containing atmosphere, a reduction temperature of 300-500° C., a reduction pressure of 0-3 MPa, and a reduction time of 1-6 h.
32. The method according to claim 31, wherein: The reduction conditions include: under a hydrogen-containing atmosphere, a reduction temperature of 350-450° C., a reduction pressure of 0.5-1.5 MPa, and a reduction time of 2-4 h.
33. The method according to claim 31 or 32, wherein: The volume fraction of hydrogen in the hydrogen-containing atmosphere is 10-100v%.
34. The method of claim 33, wherein: The volume fraction of hydrogen in the hydrogen-containing atmosphere is 60-100v%.
35. The method according to claim 31 or 32, wherein: The volume space velocity of hydrogen in the hydrogen-containing atmosphere is 500-4000h -1 .
36. The method of claim 35, wherein: The volume space velocity of hydrogen in the hydrogen-containing atmosphere is 1500-3000h -1 .
Citation Information
Patent Citations
Fuel oil deep-adsorption desulfurizationn catalyst, preparation method and application thereof
CN104056632A
Desulfurization adsorbent and preparation method and application thereof
CN101934218A